The "Petri" Dish: A Case of Simultaneous Invention in Bacteriology. Issue 1 (March 2019) - Shama, Gilbert
Highlights: The bacteriological zeitgeist at the turn of the 19th century is portrayed. Koch's use of glass plates for culturing bacteria came to revolutionise bacteriology. Two-component glass culture dishes constitute a simultaneous invention. Abstract: Richard Julius Petri's status as inventor of the culture dish that bears his name has been subject to a number of challenges over the years. Both those bacteriologists who claimed self-recognition for the invention, and those to whom it was attributed by their various advocates were all contemporaries of Petri. The evidence assembled here indicates that no single individual—including Petri—ought to be accorded credit for the inception of that shallow, circular, covered culture dish which, it transpires, is a simultaneous invention made by half a dozen bacteriologists active in the mid-1880s and ultimately owes its emergence to the prevailing bacteriological zeitgeist .